ΛΛ̄ production in two-photon interactions - Anderson, S; Kubota, Y; Lattery, M; O'Neill, J; Patton, S; Poling, R; Riehle, T; Savinov, V; Smith, A; Alam, MS; Athar, S; Ling, Z; et al. (1997)
Using the CLEO detector at the Cornell e+e- storage ring CESR we study the two-photon production of ΛΛ̄, making the first observation of γγ→ΛΛ̄. We present the cross section for γγ→ΛΛ̄ as a function of the γγ center of mass energy and compare it to that predicted by the quark-diquark model.